Regulatory Function of Sympathetic Innervation on the Endo/Lysosomal Trafficking of Acetylcholine Receptor - Straka, Tatjana; Schröder, Charlotte; Roos, Andreas; Kollipara, Laxmikanth; Sickmann, Albert; Williams, Marion Patrick Ivey; Hafner, Mathias; Khan, Muzamil Majid; Rudolf, Rüdiger (Frontiers in Physiology, 2021)
Recent studies have demonstrated that neuromuscular junctions are co-innervated by sympathetic neurons. This co-innervation has been shown to be crucial for neuromuscular junction morphology and functional maintenance. To improve our understanding of how sympathetic innervation affects nerve-muscle synapse homeostasis, we here used in vivo imaging, proteomic, biochemical and microscopic approaches to compare normal and sympathectomized mouse hindlimb muscles. Live confocal microscopy revealed reduced fiber diameters, enhanced acetylcholine receptor turnover, and increased amounts of endo/lysosomal acetylcholine-receptor bearing vesicles. Proteomics analysis of sympathectomized skeletal muscles showed that besides massive changes in mitochondrial, sarcomeric, and ribosomal proteins, the relative abundance of vesicular trafficking markers was affected by sympathectomy. Immunofluorescence and Western blot approaches corroborated these findings and, in addition, suggested local upregulation and enrichment of endo/lysosomal progression and autophagy markers, Rab 7 and p62, at the sarcomeric regions of muscle fibers and neuromuscular junctions. In summary, these data give novel insights into the relevance of sympathetic innervation for the homeostasis of muscle and neuromuscular junctions. They are consistent with an upregulation of endocytic and autophagic trafficking at the whole muscle level and at the neuromuscular junction.